Identifikasi Tumbuhan Famili Malvaceae Di Kawasan Cigagak, Cipadung Kecamatan Cibiru - Nisa Kartika; Nisrina Humaira (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
Malvaceae is a plant family that is often known as the cotton tribe. Malvaceae is known as a plant that has various benefits both in the health sector as medicine, industry, art, ecological interests, and others. Generally, the Malvaceae family is found in bush or shrub habitus and is rarely found in tree form. The research aimed to find out how many families Malvaceae grow in a field and to be able to identify and classify the plants found in an area. In the research that has been conducted, 4 individual plants have been found, consisting of 2 Balsa species, 1 hibiscus plant, and 1 pulutan plant. Hibiscus and pulutan plants are widely used as medicines because they contain chemical compounds that reduce the risk of various diseases and balsa trees are used in carving as crafts, aircraft modeling, and industrial matters.